2012
DOI: 10.3892/or.2012.1814
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of neoadjuvant chemotherapy with irinotecan hydrochloride and nedaplatin followed by radical hysterectomy for bulky stage Ib2 to IIb, cervical squamous cell carcinoma: Japanese Gynecologic Oncology Group study (JGOG 1065)

Abstract: The efficacy and adverse events of neoadjuvant chemotherapy with irinotecan hydrochloride and nedaplatin were evaluated in patients with bulky stage Ib2 to IIb cervical squamous cell carcinoma. Eligibility included patients who received irinotecan (60 mg/m2) on days 1 and 8 and nedaplatin (80 mg/m2) on day 1 of a 21-day cycle. After 1-3 courses of chemotherapy, radical hysterectomy was performed. Sixty-eight patients were enrolled. Sixty-six were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…Postoperative pathological examination confirmed that there were no cancer cells in the resected tissues. Yamaguchi et al (21) treated stage IB2 and IIB cervical cancer with irinotecan and nedaplatin, with good therapeutic efficacy. Other studies suggested that the vagina and the cervix are lined with the same type of squamous cell epithelium, and several risk factors are shared by cervical and vaginal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pathological examination confirmed that there were no cancer cells in the resected tissues. Yamaguchi et al (21) treated stage IB2 and IIB cervical cancer with irinotecan and nedaplatin, with good therapeutic efficacy. Other studies suggested that the vagina and the cervix are lined with the same type of squamous cell epithelium, and several risk factors are shared by cervical and vaginal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The topoisomerase inhibitor irinotecan is a semi‐synthetic derivative of camptothecin that is converted to an active form (SN‐38). Several trials have demonstrated the clinical efficacy of irinotecan against platinum‐resistant epithelial ovarian cancer; moreover, a recent study indicated that irinotecan was active against SCC of the uterine cervix . Several dosing schedules for irinotecan have been established with the goal of maximizing the anti‐tumor effect while minimizing adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of grade 3/4 hematologic toxicity was 16.7% for neutropenia, 18.4% for anemia, and 2.0% for febrile neutropenia, but there was no grade 3/4 thrombocytopenia. The Japanese Gynecologic Oncology Group evaluated the efficacy and safety of combination chemotherapy comprising irinotecan 60 mg/m 2 on days 1 and 9 and nedaplatin 80 mg/m 2 every three weeks as neoadjuvant chemotherapy for patients with stage IB2–IIB uterine cervical squamous cell carcinoma 40. The response rate was 75.8%, which included two patients with a complete response, 48 with a partial response, 12 with stable disease, and 0 with progressive disease, with four patients not evaluated.…”
Section: Clinical Findingsmentioning
confidence: 99%